PENERAPAN EFEKTIVITAS RELAKSASI BENSON TERHADAP KUALITAS TIDUR PADA PASIEN CHRONIC KIDNEY DISEASE (CKD) YANG MENJALANI HEMODIALISIS DI RSUD TARAKAN JAKARTA PUSAT - Dewi, Ratna; Irawati, Diana; Anggaraini, Dewi; Jumaiyah, Wati; Suryanti, Asih Dwi (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Background: Hemodialysis patients can experience psychological problems such as: stress, anxiety, depression, and insomnia or disturbed sleep quality. Prolonged sleep quality disturbances can have an impact on the patient's quality of life, thus requiring interventions that are safe and easy to implement, one of which is Benson relaxation. The aim of applying Benson's relaxation to sleep quality in chronic kidney disease (CKD) patients undergoing hemodialysis. The application of evidence based nursing practice (EBNP) is through literature searches via the PubMed data base with the final result being an article entitled "The Effect of Benson's Relaxation Technique on the Quality of Sleep of Irian Hemodialysis Patients: A Randomized Trial" in the form of a randomized controlled trial with pre -post-test design. The sampling technique used G*Power based on effect size = 0.73, power of 0.8, and ? = 0.05 with 44 hemodialysis patients (22 intervention group and 22 control group) at Tarakan Hospital, Central Jakarta. The application of Benson relaxation is carried out for 20 minutes, 2 times a day 3 days per week for 4 weeks from June 16 to July 15 2023. Sleep quality data was collected using the PSQI questionnaire before and after the intervention with paired t-test and independent sample test. t-test. The results of the implementation showed that the sleep quality score after the intervention had improved (p value 0.002) in the intervention group, while the sleep quality score did not improve in the control group (p value 0.061). The calculated t value between the intervention group and the control group was 2.894 (p value 0.006), so there was a significant difference in sleep quality between the two groups. Conclusion: there was an increase in the sleep quality score of hemodialysis patients in the intervention group and there was a difference in the average quality score after Benson relaxation between the intervention group and the control group. Suggestion: Benson relaxation can be used as a nursing intervention for hemodialysis patients as a measure to prevent sleep quality disorders.